Natural deep eutectic liquid and ultrasound-assisted extraction of milk thistle phenolics and their hepatoprotective activities - Nasrullah, Nabiha; Akram, Sumia; Rashid, Ayoub; Adnan, Ahmad; Mushtaq, Muhammad (Frontiers in Sustainable Food Systems, 2024)
Introduction The present research describes the utilization of natural deep eutectic solvent in combination with ultrasound for the extraction of milk thistle polyphenols. The extracts obtained under different conditions were evaluated for their in vitro antioxidant activities and hepatoprotective activities in Albino mice (in vivo). Methods The extraction parameters involving liquid-to-solid ratio (S/L), ethanol-to-natural deep eutectic solvent ratio (EtOH/DES), extraction time (t), and ultrasound treatment time were investigated and optimized to enhance the recovery of bioactives, their phenolic content, Trolox equivalent antioxidant capacity (TEAC), and radical scavenging capacity (RSC). Results and discussions The extraction of milk thistle polyphenols using glucose/citric acid (1:1)-based natural deep eutectic liquid coupled with ultrasound for 1.0 min under an S/L of 6.2, EtOH/DES 9, and extraction time of 120.8 min offered 35.89 ± 2.29 g/100 g of crude extracts, which were three-fold higher than that by conventional solvent extraction (CSE). Each gram of milk thistle extracts thus obtained comprised 377.93 ± 6.17 mg GAE of TPC and exhibited 298.70 ± 3.06 μmol TEAC and 93.16 ± 0.58 percent inhibition of DPPH free radicals. In addition, the administration of milk thistle extracts obtained as given above at 25 mg/Kg body weight in Albino mice significantly (p ≤ 0.05) improved the liver function parameters at the end of treatment (7 days). Conclusion Overall, it was observed that NaDES in combination with medium-level ultrasound energy (700 watt) might work as a sustainable choice to enhance the recovery of bioactive phenolics from milk thistle powder without compromising their antioxidant and hepatoprotective potential.